Sources of Stress among Pre-Service Language Teachers: A Quantitative Investigation - Claire Napthalie Somoso (International Journal on Integrated Education, 2022)
This study investigated the sources of stress of 61 Pre-service Language Teachers in Western Mindanao State University using the Undergraduate Sources of Stress (USOS) Questionnaire developed by Blackmore and Jones (2005). A descriptive-quantitative design was utilized to determine these sources of stress and to identify whether there is a significant difference in the sources of stress across genders. The results and findings of the study showed that academic-related concerns are the main sources of stress for the majority of pre-service language teachers. Also, it appeared that male and female respondents do not significantly differ in their sources of stress. These findings contributed new insights with regards to the scarcity of studies conducted which aimed to determine the sources of stress among undergraduate students, specifically, among Preservice Language Teachers in the Philippines.